Financial Intermediation, Loanable Funds, and The Real Sector - Holmstrom, B.; Tirole, J. (Quarterly Journal of Economics, 1997)
We study an incentive model of financial intermediation in which firms as well as intermediaries are capital constrained. We analyze how the distribution of wealth across firms, intermediaries, and uninformed investors affects investment, interest rates, and the intensity of monitoring. We show that all forms of capital tightening (a credit crunch, a collateral squeeze, or a savings squeeze) hit poorly capitalized firms the hardest, but that interest rate effects and the intensity of monitoring will depend on relative changes in the various components of capital. The predictions of the model are broadly consistent with the lending patterns observed during the recent financial crises.